Implementing Problem-Based Learning with Teaching at The Right Level Approach to Improve Numeracy Literacy - Susanti, Vera Dewi; Wati, Junita Ulfa Munah; Sulastri, Yuliana Endang (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2024)
This study aimed to improve students' numeracy literacy skills by implementing the Problem-Based Learning model with the Teaching at The Right Level approach. The study was conducted in Class X DPIB 1 SMKN 1 Kota Madiun, Kartoharjo District. Thirty-six students participated in this study, with 30 males and six females as samples. In the 2023-2024 academic year, the research period took place from February to May, beginning the second semester. The study was conducted in two cycles, with four sessions, each meeting lasting 2 JP (2 x 45 minutes). Class X DPIB 1 students had an average numeracy literacy ability score of 55.50 in the Cycle 1 evaluation. This indicates that there is still considerable room for improvement. In addition, most students have not met the minimum required level of completeness, as seen from the percentage of classical completeness, which only reached 36.11% (13 students scored â‰¥ 75). Meanwhile, the analysis of the data from cycle 2 showed that there were no students in the inferior category, two students in the poor category, five in the pretty good category, twenty-two in the excellent category, and seven in the outstanding category. The implementation of cycle 2 showed a significant increase, where the average score of numeracy literacy skills of class X DPIB 1 students increased to 72.94, and the percentage of classical completion also increased to 58.33% (21 students scored â‰¥75). Students' numeracy literacy skills can be improved by combining the Problem-Based Learning model with the Teaching at The Right Level Approach.